The role of exchange rate in supporting trade balance in Vietnam - Lan Huong Hoang (Graduate Institute of International and Development Studies, 2016)
In this paper, I apply a multivariate Structural Vector Autoregressive (SVAR) and Vector Error correction model (VECM) to analyze short-term and long-term effects of foreign exchange rate on trade balance of Vietnam, using monthly data from 2004-2015. Real effective exchange rate is used to reflect overall performance of Vietnam's currency. The results suggest that in short-term, exchange rate has very limited impacts on trade flows; while in longer horizon, it does not affect imports in either nominal or real terms but has strong effect on nominal exports. To the extent of this research, there is a number of policy implications has been made to support policy makers in Vietnam.
Keywords: 330